Diagnostic Accuracy of Carotid Doppler Ultrasound for Detection of Carotid Artery Stenosis in Ischemic Stroke Patients: Keeping Computed Tomography Angiography as the Gold Standard - Sarfraz, Sahr; Muhammad, Dost; khan, Muhammad Babar; Sanaullah, .; Sarshar, Sahar; Itrat, Zara (Biological and Clinical Sciences Research Journal, 2025)
Carotid artery stenosis is a significant risk factor for ischemic stroke. Early and accurate identification of stenosis is critical for preventing stroke recurrence and improving clinical outcomes. Carotid Doppler Ultrasound (CDU) offers a non-invasive, bedside screening modality, but its diagnostic accuracy compared to Computed Tomography Angiography (CTA) requires further evaluation. Objective: To assess the diagnostic accuracy of CDU in detecting carotid artery stenosis in ischemic stroke patients, CTA was used as the reference standard. Methods: This diagnostic accuracy study was conducted at Combined Military Hospital (CMH), Kharian, and included 95 patients with ischemic stroke who underwent both CDU and CTA. CDU was performed by experienced sonographers, assessing stenosis using peak systolic velocity and intima-media thickness. CTA was interpreted by radiologists blinded to CDU findings. The diagnostic performance of CDU was measured in terms of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, with CTA serving as the gold standard. Results: Among the 95 patients, CDU demonstrated a sensitivity of 91%, specificity of 77%, PPV of 47.3%, NPV of 92.5%, and overall diagnostic accuracy of 80%. CDU showed strong performance in identifying patients without significant stenosis but had moderate specificity in confirming the presence of stenosis. Conclusion: CDU is a valuable screening tool for carotid artery stenosis in ischemic stroke patients, particularly in settings with limited access to advanced imaging. However, confirmatory CTA remains necessary for definitive diagnosis due to its limited specificity and PPV. When supported by appropriate follow-up imaging, integrating CDU into stroke workups can enhance early detection and streamline care pathways.